2017
DOI: 10.3168/jds.2016-11933
|View full text |Cite
|
Sign up to set email alerts
|

Citizens' views on the practices of zero-grazing and cow-calf separation in the dairy industry: Does providing information increase acceptability?

Abstract: The primary aim of this study was to assess the influence of provision of information on lay citizens' opinions regarding 2 common management practices, zero-grazing and cow-calf separation. To aid in the interpretation of the findings, our secondary aim was to explore the awareness and opinions of Brazilian citizens about these practices. We surveyed a convenience sample of Brazilian citizens (192 men and 208 women), recruited in a public place, with the majority stating that they were largely unfamiliar with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 54 publications
7
130
2
2
Order By: Relevance
“…Farmers and other industry stakeholders should be made aware of the potential repercussions to the dairy industry of consumers' growing concerns towards animal welfare (VON KEYSERLINGK & HÖTZEL, 2015). Recent research has shown that Brazilians (HÖTZEL et al, 2017), like citizens from other countries (ELLIS et al, 2009;CARDOSO et al, 2016a) are concerned with dairy cattle welfare and reject some of the practices reported to be prevalent in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Farmers and other industry stakeholders should be made aware of the potential repercussions to the dairy industry of consumers' growing concerns towards animal welfare (VON KEYSERLINGK & HÖTZEL, 2015). Recent research has shown that Brazilians (HÖTZEL et al, 2017), like citizens from other countries (ELLIS et al, 2009;CARDOSO et al, 2016a) are concerned with dairy cattle welfare and reject some of the practices reported to be prevalent in this study.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence has shown that the public considers pasture access for dairy cows important (Schuppli et al, 2014;Hötzel et al, 2017) and that cows value access to pasture, especially at night (e.g., Legrand et al, 2009;Charlton et al, 2013;von Keyserlingk et al, 2017). Cows may use indoor housing as protection from rainfall (Legrand et al, 2009;Charlton et al, 2011aCharlton et al, , 2013 and solar radiation (Schütz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, given that production and fertility are important to farm profitability, those involved with animal production have traditionally taken a pragmatic approach to welfare and often emphasize factors that improve biological functioning (e.g., health, fertility, production; Te Velde, Aarts, & Van Woerkum, ; Verbeke, ). Conversely, lay citizens often place more emphasis on natural living (see, e.g., Cardoso, Hötzel, Weary, Robbins, & von Keyserlingk, ; Hötzel, Cardoso, Roslindo, & von Keyserlingk, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, given that production and fertility are important to farm profitability, those involved with animal production have traditionally taken a pragmatic approach to welfare and often emphasize factors that improve biological functioning (e.g., health, fertility, production; Te Velde, Aarts, & Van Woerkum, 2002;Verbeke, 2009). Conversely, lay citizens often place more emphasis on natural living (see, e.g., Cardoso, Hötzel, Weary, Robbins, & von Keyserlingk, 2016;Hötzel, Cardoso, Roslindo, & von Keyserlingk, 2017). Fraser et al (2013) suggest that animal science diverges from animal welfare science insofar as the former has traditionally emphasized efficiency or productivity at the farm level, while the latter focuses on the individual animal, with herd-level functioning as an associated outcome.…”
mentioning
confidence: 99%